Zarządzanie wiedzą w fazie zakończenia projektu informatycznego - Wojtkiewicz-Wydra, Ewa (Knowledge management in the final phase of IT project, 2006)
In the first part of the article the conception of knowledge management is described. Author proposed integration of two paths: the human resources path and the information systems path. The main aim of this part of the paper is the creation of total knowledge management conception. Therefore the author decided to add three levels: organization, team and individual. The next part of the article focuses on the explanation of the knowledge processes which proceed during IT projects realization. It is an introduction to the description of the meaning of knowledge management in the final part of IT projects, because at the end of the article the author created and described the model of this process.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1134, s. 281-292